EFEKTIVITAS GAYA KEPEMIMPINAN KOLABORATIF (STUDI KASUS PADA SEKOLAH TINGGI ILMU ADMINISTRASI TABALONG) - Isnawati Deayana; Muslih Ambri; Muhammad Riduansyah Syafari (stiatabalong.ac.id, 2021)
This research aims to find out the effectiveness of collaborative leadership styles at STIA Tabalong by using qualitative research methods Sampling techniques using purposive sampling, i.e. chosen with specific considerations and objectives. The informants in this study are employees or academic community in STIA Tabalong. Data collection using interviews in depth. Data analysis techniques, meanwhile, use interactive models. The results showed that the collaborative leadership style at STIA Tabalong was effective. This is illustrated from the findings of research showing that the collaborative leadership style is well received by employees, increased leadership capabilities, leaders who are able to read the work climate situation, factors that influence leadership skills such as educational factors, experience, and the wide range of associations, as well as employees who are willing to adjust their way of thinking and act in the interests of together. Keywords: Effectiveness of Leadership, Collaborative Leadership Style.